Governance of the Development of the Special Economic Zone (SEZ) Galang Batang, Riau Islands - Al Anshori, Milyan Risydan; Hidayat, Rahmat; Madya, Faisal (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The Galang Batang Special Economic Zone (SEZ) is a strategic initiative by the Indonesian government aimed at enhancing economic growth through mineral downstreaming and logistics. This study investigates the governance of the Galang Batang SEZ, identifying key challenges such as ineffective supervision, inefficient licensing processes, and limited technological integration. The research employs a qualitative approach, utilizing in-depth interviews, document analysis, and direct observations to evaluate existing policies and the role of the Directorate General of Customs and Excise (DJBC) as a trade facilitator. Findings indicate that despite its advantageous geographical location, the SEZ has not fully realized its potential due to governance issues. The DJBC has positively impacted customs procedures but requires improved cross-sector coordination. The study concludes that enhanced governance, technological infrastructure, and policy synergies are critical for maximizing the SEZ's potential as a mineral processing hub. Recommendations include optimizing DJBC's role, developing human resource capacities, and fostering private sector collaboration to ensure sustainable economic growth. This research fills existing gaps in literature regarding the specific governance challenges faced by the Galang Batang SEZ and its integration into global value chains, providing insights for policymakers to enhance regional economic development.